The Effect of Edutainment Learning Methods on Fifth-Grade Students’ Learning Outcomes in Theme 8 of Our Friend Environment - Eanassyalili Jasika Siregar; Patri Janson Silaban; Candra Ronitua Gultom; Bogor Lumban Raja; Rumiris Lumban Gaol (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper presents the effect of using the Edutainment learning method on students’ learning outcomes on theme 8 of our friend environment in class V at SD Negeri 068006 Simalingkar in the academic year 2022/2023. The research uses quantitative methods. The research population was 245 students from all grades I-VI at SD Negeri 068006 Simalingkar. Sampling uses a purposive sample and the sample used involved 30 fifth-grade students. The research results indicate that students’ learning outcomes using the Edutainment learning method are included in the very good category with an average score of 81.86 with a correlation test result of 0.634, which means rcount (0.634) ≥ rtable (0.361), thus Ha is accepted. Therefore, there is a considerable effect between the use of the Edutainment learning method and students’ learning outcomes in class V at SD Negeri 068006 Simalingkar. It can be seen from the research results of the T-test, where rcount 4.335 ≥ rtable 2.048, Ha is also accepted. It implies that there is a significant positive effect from the use of the Edutainment learning method on students’ learning outcomes in theme 8 of our friend environment in class V at SD Negeri 068006 Simalingkar in the academic year 2022/2023.